Diffusion of Innovation in Hospitals: Exploring the Benefits and Challenges of Using Instagram - Herna Herna; Putri Risa Ramadani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
Instagram is a potential platform for disseminating information to the public, mainly health-related information. The Tanah Abang Regional General Hospital (RSUD Tanah Abang) has adopted Instagram as a medium for providing health information and services. This study aims to analyze the utilization of Instagram by RSUD Tanah Abang as an information platform for the public. The research used a qualitative approach with a constructivist paradigm, employing the Diffusion of Innovation theory as an analytical tool. Data was collected through observations of the @rsudtanahabang account and in-depth interviews with the public relations team and its followers. The findings show that RSUD Tanah Abang adopted Instagram due to its relative advantages over conventional media, such as fast information dissemination, two-way interaction capabilities, and ease of developing engaging content. The @rsudtanahabang account successfully increased public engagement in conveying health information. Interactive features like Instagram Feed, Stories, Reels, and Instagram Live strengthen the two-way interaction between the hospital and the public. Content on @rsudtanahabang is dynamically and regularly managed, following social media trends to ensure the information remains relevant and engaging. Instagram has proven to be a compatible tool for disseminating service-related information, such as doctor schedules, strategic health issues, treatment procedures, and health education. However, several challenges were identified and deemed necessary by the hospital, including (1) maintaining the consistency of information shared through Instagram. The hospital must ensure that the content published is always accurate, relevant, and adheres to medical protocols, and (2) managing negative comments responsively and professionally to preserve the hospital’s reputation.